ASSISTIVE TECHNOLOGIES FOR VISUALLY IMPAIRED STUDENTS - Turg’unboyeva Zulxumor Ibragimovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article talks about assistive technologies and their importance, aimed at ensuring that visually impaired students with special educational needs can read through assistive technologies.